Reconstruction of the Consonant Phoneme of Proto Rio De Panagim (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The Linggi dialect is reported to have its own phonological structure, distinguishing it from its closest Melaka-Johor-Riau variant. A historical linguistic investigation was done in the Kuala Linggi region, also known as Rio De Panagim, to determine the extent to which this Malay dialectal phenomenon is parallel. The data observation procedure for the application of the historical linguistic theory of structuralism in the North Melaka region involves a total of eight focal areas. The techniques used in the field include dialogue, recording, interview, acting, and the submission of photos. The first finding of this study shows that the ancient form of Kuala Linggi (Proto-Malay dialect of Kuala Linggi) has 18 ancient consonants, namely *p, *b, *t, *d, *k, *ɡ, *m, *n, *ɲ, *ŋ, *s, *ɣ, *h, *tʃ, *ʤ, *l, *w, and *j. Secondly, on the basis of the retention of Proto-Malayic characteristics at the initial syllable and the last closed syllable, this study suggests that the Kuala Linggi dialect is more identical to the Melaka-Johor variant than the Linggi-Negeri-Sembilan variant. This simultaneously positions the Kuala Linggi dialect under the Melaka-Johor variation branch and at the borderline of the Linggi mixed dialect’s spread. However, this conclusion is far from convincing based on this small study alone. Therefore, this study strongly suggests that these findings be strengthened by additional research on Kuala Linggi diphthongs and vowels, thereby completing the historical linguistics study of the region. Full text: PDF